Therapeutic Effect of Microcurrent Therapy in Children With In-toeing Gait Caused by Increased Femoral Anteversion: A Pilot Study - Ahn, Jae Ki (Ann Rehabil Med, 2017)
OBJECTIVE: To investigate the efficacy of portable microcurrent therapy device (PMTD) of the hip internal rotators in the treatment of in-toeing gait caused by increased femoral anteversion in children over 8 years of age. METHODS: Eleven children (22 legs; 4 boys and 7 girls; mean age, 10.4±1.6 years) with in-toeing gait caused by increased femoral anteversion were included in the present study. All children received 60 minutes of PMTD (intensity, 25 µA; frequency, 8 Hz) applied to the hip internal rotators daily for 4 weeks. Hip internal rotation (IR) angle, external rotation (ER) angle, and midmalleolar-second toe angle (MSTA) measurement during stance phase at transverse plane and Family Satisfaction Questionnaire, frequency of tripping and fatigue like pains about the PMTD were performed before treatment and at 4 weeks after initial PMTD treatment. Paired t-test and Fisher exact test were used for statistical analysis. RESULTS: Hip IR/ER/MSTA was 70.3°±5.4°/20.1°±5.5°/–11.4°±2.7°, and 55.7°±7.8°/33.6°±8.2°/–2.6°±3.8° before treatment and at 4 weeks after initial PMTD treatment, respectively (p<0.01). Ten of 11 (91%) children's family stated that they were generally satisfied with the PMTD treatment. The frequency of tripping and fatigue like pains was significantly lower at 4 weeks after PMTD treatment (p<0.05). Excellent inter-rater and intra-rater reliability was observed for repeated MSTA measurements between the examiners (k=0.91–0.96 and k=0.93–0.99), respectively. CONCLUSION: PMTD of the hip internal rotators can be effective in improving the gait pattern of children with in-toeing gait caused by increased femoral anteversion.